Colonnaded streets within the roman cityscape: a “spatial” perspective - Rababeh, Shaher; Al Rabady, Rama; Abu-Khafajah, Shatha (Journal of Architecture and Urbanism, 2014)
Studies tackling the Roman legacy of colonial cities and Arabian provinces are still grappling with these cities from an urban planning perspective and/or building typologies. They do not provide a ‘spatial’ analysis that allows reading the Roman cities through the features that structured its urban language; one of which is the colonnaded streets. The study adopts a holistic approach to confront the ambiguities about possible origins, uses and meanings of the Roman colonnaded streets when traced in the Roman East as well as other Western cities. Besides its utilitarian and cultural value, the colonnaded streets are nalyzed according to two interrelated interpretations: astrological interpretation to represent an empire of astral divinity and performative interpretation to represent an empire of imperial power. The colonnaded streets is transformed from a ‘line on site’ into a ‘line of sight’ that testifies to the social norms of the Roman people but also to their ideologies, beliefs, and aspirations.